Pengembangan Media Pembelajaran Augmented Reality (AR) pada Pembelajaran Perangkat Keras Komputer di SMK Al-Aziziyah Candi - Syarif, Abril Umar; Astuti, Cindy Cahyaning (Universitas Trunojoyo Madura, 2023)
A good learning process must contain interactive, fun, challenging, motivating aspects and provide more space for students to be able to develop creativity and independence. For this reason, in realizing effective learning media, it is necessary to use technology in the field of education, namely learning media using virtual technology or often referred to as AR. This development research uses the ADDIE development model (analyze, design, development, implementation, evaluation). The purpose of this research is to develop AR learning media on computer hardware learning at SMK Al Aziziyah Candi. Based on the results of the development of AR learning media, computer hardware has been developed and is very feasible to use. The results of validation by media experts and material experts on the products developed include indicators of media quality, presentation, language, material content and language. Based on the results of validation by media experts and material experts obtained validity with a percentage of media experts 94%, material experts 95%, and small-scale trials with a percentage of 91.25% with very feasible and usable criteria.